DECENTRALIZATION AND RELIGIOUS IDENTITY IN POST–NEW ORDER INDONESIA: A SOCIAL HISTORY OF ISLAMIC MODERATION AND LOCAL GOVERNANCE (1998–PRESENT) - Mohammad Syawaluddin; M.Husni Candra; Muhammad Husni; Tjik Harusn (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2026)
From a social history perspective, decentralization influenced not only political institutions but also everyday social life. Local elites often used religious symbols and narratives to gain legitimacy and strengthen their political influence. In several regions, this process contributed to the emergence of faith-based local regulations. One example is the implementation of Islamic law in Aceh, where regional autonomy allowed religious norms to become integrated into governance and public life.However, decentralization also produced complex consequences. Although autonomy was intended to strengthen democracy and accommodate local diversity, it sometimes intensified identity-based politics. Religious discourse could be used strategically by political actors to gain support and authority. As a result, debates about religious identity often overshadowed broader social issues such as poverty, inequality, and corruption. This study shows that Islamic moderation in post–New Order Indonesia has developed through interactions between local communities, religious institutions, and political actors within decentralized governance structures.